--- a/Tutorial/Tutorial3.thy Fri Jan 21 22:02:34 2011 +0100
+++ b/Tutorial/Tutorial3.thy Fri Jan 21 22:23:44 2011 +0100
@@ -6,12 +6,12 @@
text {*
Barendregt's proof needs in the variable case a case distinction.
- One way to do this in Isar is to use blocks. A block is some sequent
- or reasoning steps enclosed in curly braces
+ One way to do this in Isar is to use blocks. A block consist of some
+ assumptions and reasoning steps enclosed in curly braces, like
{ \<dots>
-
have "statement"
+ have "last_statement_in_the_block"
}
Such a block can contain local assumptions like
@@ -25,7 +25,7 @@
Where "C" is the last have-statement in this block. The behaviour
of such a block to the 'outside' is the implication
- \<lbrakk>A; B\<rbrakk> \<Longrightarrow> "C"
+ A \<Longrightarrow> B \<Longrightarrow> C
Now if we want to prove a property "smth" using the case-distinctions
P1, P2 and P3 then we can use the following reasoning:
@@ -52,17 +52,12 @@
P2 \<Longrightarrow> smth
P3 \<Longrightarrow> smth
- If we know that P1, P2 and P3 cover all the cases, that is P1 \<or> P2 \<or> P3 is
- true, then we have 'ultimately' established the property "smth"
+ If we know that P1, P2 and P3 cover all the cases, that is P1 \<or> P2 \<or> P3
+ holds, then we have 'ultimately' established the property "smth"
*}
-section {* EXERCISE 7 *}
-
-text {*
- Fill in the cases 1.2 and 1.3 and the equational reasoning
- in the lambda-case.
-*}
+subsection {* Two preliminary facts *}
lemma forget:
shows "atom x \<sharp> t \<Longrightarrow> t[x ::= s] = t"
@@ -78,6 +73,14 @@
(auto simp add: lam.fresh fresh_at_base)
+
+section {* EXERCISE 7 *}
+
+text {*
+ Fill in the cases 1.2 and 1.3 and the equational reasoning
+ in the lambda-case.
+*}
+
lemma
assumes a: "x \<noteq> y"
and b: "atom x \<sharp> L"
@@ -111,12 +114,12 @@
qed
next
case (Lam z M1) -- {* case 2: lambdas *}
- have ih: "\<lbrakk>x \<noteq> y; atom x \<sharp> L\<rbrakk> \<Longrightarrow> M1[x::=N][y::=L] = M1[y::=L][x::=N[y::=L]]" by fact
+ have ih: "\<lbrakk>x \<noteq> y; atom x \<sharp> L\<rbrakk> \<Longrightarrow> M1[x ::= N][y ::= L] = M1[y ::= L][x ::= N[y ::= L]]" by fact
have a1: "x \<noteq> y" by fact
have a2: "atom x \<sharp> L" by fact
- have fs: "atom z \<sharp> x" "atom z \<sharp> y" "atom z \<sharp> N" "atom z \<sharp> L" by fact+
+ have fs: "atom z \<sharp> x" "atom z \<sharp> y" "atom z \<sharp> N" "atom z \<sharp> L" by fact+ -- {* !! *}
then have b: "atom z \<sharp> N[y::=L]" by (simp add: fresh_fact)
- show "(Lam [z].M1)[x::=N][y::=L] = (Lam [z].M1)[y::=L][x::=N[y::=L]]" (is "?LHS=?RHS")
+ show "(Lam [z].M1)[x ::= N][y ::= L] = (Lam [z].M1)[y ::= L][x ::= N[y ::= L]]" (is "?LHS=?RHS")
proof -
have "?LHS = \<dots>" sorry
@@ -130,7 +133,7 @@
text {*
Again the strong induction principle enables Isabelle to find
- the proof of the substitution lemma automatically.
+ the proof of the substitution lemma completely automatically.
*}
lemma substitution_lemma_version: